Effect of different polysaccharides and crosslinkers on echium oil microcapsules. (5th October 2016) - Comunian, Talita A.; Gomez-Estaca, Joaquin; Ferro-Furtado, Roselayne; Conceição, Gelson José Andrade; Moraes, Izabel Cristina Freitas; de Castro, Inar Alves; Favaro-Trindade, Carmen S.
Highlights: Echium oil was protected from oxidation by encapsulation using different polysaccharides. Cashew gum can be used as wall material in complex coacervation process. Sinapic acid can be used as crosslinker instead of toxic and expensive ones. Gelatin-arabic gum capsules crosslinked with sinapic acid showed better oil stability. Crosslinked echium capsules showed resistance to different stress conditions. Abstract: Microencapsulation by complex coacervation using gelatin and arabic gum (AG) as wall materials and transglutaminase for crosslinking is commonly used. However, AG is only produced in a few countries and transglutaminase is expensive. This work aimed to evaluate the encapsulation of echium oil by complex coacervation using gelatin and cashew gum (CG) as wall materials and sinapic acid (S) as crosslinker. Treatments were analyzed in relation to morphology, particle size, circularity, accelerated oxidation and submitted to different stress conditions. Rounded microcapsules were obtained for treatments with AG (45.45 μm) and microcapsules of undefined format were obtained for treatments with CG (22.06 μm). The S incorporation for 12 h improved the oil stability by three fold compared to oil encapsulated without crosslinkers. Treatments with CG and S were resistant to different stress conditions similar to treatments with AG and transglutaminase, making this an alternative for delivery/application of compounds in food products.